Performance enhancement and integrating renewable energy into reverse osmosis seawater desalination system in the Moroccan coastal region - Otman Abida; Hanane Ait Lahoussine Ouali; Nouhaila Belkaid; Mohamed Essalhi; Emil Obeid; Nisar Ali (Cleaner Engineering and Technology)
This study investigates the energy consumption and environmental challenges of the Phosboucraa seawater desalination plant in Laayoune, southern Morocco, used as a work-study to explore strategies for enhancing energy efficiency, carbon mitigation and sustainability. The plant, which produces 4000 m3/day of fresh water for phosphate washing, currently operates at a high energy demand of approximately 8 kWh/m3. To address these challenges, four strategic scenarios were evaluated: the implementation of Pressure Exchanger (PX) technology, Ultrafiltration (UF), a single sand filter type, and the integration of renewable energy sources into the desalination process. Key findings indicate that PX technology significantly reduced energy consumption to 2.8 kWh/m3, while UF pretreatment provided a balanced outcome with a permeate flow rate of 78.62 m3/h at 2.88 kWh/m3. The single trilayer sand filter scenario achieved the highest permeate flow rate of 82.18 m3/h, but at a higher energy consumption of 3.01 kWh/m3. The optimal hybrid renewable energy system, comprising a 233 kW Photovoltaic (PV) panel, two 1500 kW wind turbines (WTs), a 965 kW converter, a 2100 kW diesel generator, and 3963 batteries, achieved the lowest Levelized Cost of Energy (LCOE) at 0.194 $/kWh and the lowest Net Present Cost (NPC) of 21.9 million $, with a renewable fraction of approximately 80.5 %. The integration of renewable energy sources led to a substantial reduction in CO2 emissions, decreasing by approximately 80 % compared to conventional diesel-powered operations. Future work will focus on integrating battery storage and developing intelligent control mechanisms to improve system stability and reliability, making hybrid desalination systems a key solution for water security in energy-resource-rich coastal regions.